ON THE REPRESENTATION OF FUNCTIONS BY SERIES OFLEGANDRE POLYNOMIALS IN WEIGHTED L_μ ^q[-1, 1] SPACES - Grigorian, M. G.; Sargsyan, A. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
In this paper we construct the weighted L_μ ^q[-1, 1], q [1, 4/3][4, +∞], and Legander series _k=1 ^∞ c_pP_k(x), which is universal in L_μ ^q [-1, 1].